Binge-Eating Disorder and Obesity in Women: The Role of Attachment States of Mind - Maxwell, Hilary (Université d'Ottawa / University of Ottawa, 2017)
There is evidence that functions related to attachment may play an important role in the etiology and maintenance of eating disorders, particularly anorexia and bulimia nervosa (Kuipers & Bekker, 2012; Tasca & Balfour, 2014). However, there is little research available on attachment functioning in those with binge-eating disorder (BED). This dissertation consists of three studies that examine the role of attachment states of mind and attachment dimensions in understanding BED and co-morbid overweight, and to examine mechanisms related to group treatment response for those with BED. The first study assessed attachment state of mind classifications (i.e., attachment categories) to understand better: 1) the psychopathology and maintenance of BED and co-morbid overweight, and 2) the treatment response of women with BED who receive Group Psychodynamic Interpersonal Psychotherapy (GPIP; Tasca, Mikail, & Hewitt, 2005). Overweight women with BED (subsequently referred to as women with BED), overweight women without BED, and normal weight women without BED completed the Adult Attachment Interview (AAI; Main, Goldwyn, & Hesse, 2002). Those with BED completed the AAI pre- and six months post- GPIP and those without BED completed the AAI at one-time point. Women with BED have significantly higher rates of insecure (preoccupied) and unresolved/disorganized attachment states of mind compared to normal weight women without BED. Women with BED had similar rates of insecure and unresolved/disorganized attachment states of mind as overweight women without BED. With respect to treatment completers, changes in attachment states of mind were not statistically significant. However, follow-up analyses indicated clinically meaningful changes which are discussed in the study. The second study used attachment dimensions of coherence of mind and reflective functioning (measured using the AAI) to add to our understanding of the psychopathology and maintenance of BED and co-morbid overweight. Higher Reflective Functioning scores differentiated normal weight women from both women with BED and overweight women without BED, and the latter two groups did not differ from each other. Coherence of Mind scores did not differentiate the groups. The third study used attachment dimensions of coherence of mind and reflective functioning to understand better group psychotherapy response for those with BED who received GPIP. Greater reflective functioning at pre-treatment was associated with a decline in binge eating frequency at 12 months post-treatment. Pre-treatment levels of coherence of mind was not related to group treatment outcomes. Reflective Functioning scores significantly improved from pre- to six months post-treatment. Further, more than 39% of participants demonstrated clinically reliable improvement and almost 32% experienced clinically reliable recovery with respect to reflective functioning. These results were moderated by pre-treatment self-reported attachment anxiety. That is, those with lower attachment anxiety showed significant improvement in reflective functioning, whereas those with higher attachment anxiety did not show this improvement. A third of participants experienced clinically significant improvement in coherence of mind, but this change was not statistically significant. Overall, attachment dimensions and attachment state of mind classification contribute to our understanding of the etiology and maintenance of BED and co-morbid overweight, as well as to our understanding of the group treatment response of those with BED. Addressing attachment insecurity and low reflective functioning in those with BED may improve treatment outcomes.
Keywords: Attachment; Adult Attachment Interview; Reflective Functioning; Binge-Eating Disorder; Group Psychotherapy